Lateral Meningomyelocele in a Neonate: A Case Report - Prasad, G Raghavendra; Rashmi, TM (Journal of Neonatal Surgery, 2015)
Lateral presentation of meningocele and meningomyelocele is extremely rare. Most of the lateral meningocele described are associated with other syndromes. Isolated lateral meningomyelocele cases are rarer still. We herein report a neonate with isolated lateral gluteal meningomyelocele.